Amiloidogeni proteini kot tarča aptamerov - Kovšca, Živa (Placebo, 2024)
Neurodegenerative diseases are becoming an increasingly significant global issue. They are often associated with the misfolding of amyloidogenic proteins which can aggregate and accumulate in various regions of the central nervous system. The pathology of these diseases is still largely unexplored. Aptamers are short nucleic acids with a function similar to classical antibodies but with many advantages over them. They represent a new tool in understanding the pathophysiology of neurodegenerative diseases. Aptamers also exhibit the potential to be used as therapeutics, as there are few effective treatments which could prevent the development of the disease or at least prevent the disease progression. Early detection of neurodegenerative diseases is important since the disease may be present before the onset of clinical symptoms. Aptamers are highly useful for detecting pathological proteins as they are capable of detecting specific neurotoxic conformations at low concentrations.
Keywords: amiloidogeni proteini; aptamer; Nevrodegenerativne bolezni; SELEX